The Effect of Total Deposits and Loan Arrears on the Income of CU Maju Bersama Cooperatives in Siantar District (Before and During Covid-19) - Fitri Sitinjak; Pinondang Nainggolan; Darwin Damanik; Elidawaty Purba (Budapest International Research and Critics University, 2021)
This study aims to determine the effect of total deposits and loan arrears on the income of CU Maju Bersama cooperatives in siantar district (before and during covid-19). This research method uses a quantitative research approach. The result shows that the variable amount of savings has no significant effect on the income of the CU Maju Bersama Cooperative in Siantar District. Loan arrears variable has no significant effect on the income of CU Maju Bersama Cooperative in Siantar District. (Before and During Covid-19). The test results simultaneously state that the amount of deposits and credit arrears together has a significant effect on the income of the CU Maju Bersama cooperative in Siantar District (Before and During Covid-19). The results of the R2 test state that there is an effect of the amount of deposits and credit arrears on the income of the CU Maju Bersama cooperative in Siantar District.